Ilustrasi Kritik Sosial dalam Bahasa Visual Metaphore pada Karya Mahasiswa Mata Kuliah Ilustrasi Desain sebagai Studi Kasus - Danendro Adi Adi (Humaniora, 2015)
Visual illustration does not only cover the aesthetical function, but it also becomes the main part to present visual opinion. Illustration has an ability to deliver something that not only can be seen on the surface; furthermore, it has deeper meaning than written language without to be explicit. This paper begins with a brief explanation about illustration and its visual language. Then it describes the various approaches in conveying the message and its application in illustrations. The research method used in this paper is literature study, followed by a reflective analysis of the data. At the end, article reveals a clearer picture of how ideas conveyed through visual language and its relation to deliver an opinion in a visual form.